Pre-mating Performance of Garut Ewes Fed by Sorghum-Indigofera Based Diet During the Acclimatization Period - Somanjaya, Rachmat; Fuah, Asnath Maria; Rahayu, Sri; Abdullah, Luki; Setiadi, Mohamad Agus (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study aimed to evaluate the effect of sorghum-Indigofera forage-based feed on the pre-mating performance of Garut ewes. A total of 28 Garut ewes was divided into two groups of treatment so that each treatment consisted of 14 heads. The treatment of field grass (FG) as a control and the feed composition in the formula of 50% sorghum forage silage + 40% Indigofera hay + 10% rice bran (SI). The animals were distributed under a completely randomized design, and the data were analyzed using a t-test. The results showed that the dry matter intake (DMI) and nutrient digestibility values of FG were higher (p<0.05) than SI. However, the impact on body weight gain, blood urea nitrogen (BUN) and blood cholesterol level did not differ (p>0.05). The average pre-mating bodyweight of Garut ewes for all treatments was the same number relatively, were 35 kg/head. BUN and blood cholesterol levels in the FG and SI treatments were 36.18±3.47 vs 35.27±4.23, and 66.13±5.56 vs 69.25±3.95 mg/dl, respectively. It can be concluded that SI feed had higher efficiency values and better readiness for the reproductive phase. Therefore, SI feed can be used as a substitute for field grass for the reproductive stage of Garut ewes.